Random musings : reflections of a Black intellectual - Grenway, Bernard (Hamilton Books, a member of the Rowman and Littlefield Publishing Group, 2011)
"Random Musings : Reflections of a Black Intellectual focuses on the various racial and cultural challenges facing African Americans in the context of present day educational, political, and historical realities. The text touches on a wide array of issues, including the psychology of race and power, the plight of the modern black intellectual, and the need to enhance the educational standing of American citizens across the board. Dr. Grenway uses the events of his life, in the form of random musings, to examine the much overlooked "black perspective" on American life"--Jacket